Adhesive film for surface protection, adhesive sheet, and optical member
The adhesive film formed by using a curable component containing a urethane adhesive solves the problem of low wettability and stickiness of existing surface protection films when using an acrylic adhesive in the adhesive layer. It eliminates the problem of mixture residue and achieves good pit resistance, fast recovery ability and stability under high temperature/humidity conditions, ensuring the optimization of optical performance.
Patent Information
- Application Number
- CN202410983922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-21
- Filing Date
- 2024-07-22
- Publication Date
- 2025-01-21
AI Technical Summary
When using acryloyl adhesives in the existing surface protective films, there is a problem of low wetting properties that lead to bubble trapping and adhesive residues during peeling, making it difficult to be applied to protect optical components or electronics that are susceptible to foreign matters. member.
Using a curable component containing a urethane binder, the adhesive film is formed by curing with a curing agent and has a creep dent value of less than 5%, an elastic dent value of 350MPa or greater, and 2.5gf/ inch or less peel strength and 5% or less haze.
The surface protective film can be easily removed from the adherend without deforming and/or damaging the adherend, has good pit resistance and quick recovery ability, and maintains good appearance and appearance under high temperature/humidity conditions. Peel strength stability ensures good optical properties.
Smart Images

Figure CN119331529A_ABST
Abstract
Description
[0001] Citations of Related Applications
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0095134 filed in the Korean Intellectual Property Office on July 21, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to an adhesive film, an adhesive sheet, and an optical member for surface protection. Background Art
[0004] The surface protection film is adhered to the exposed surface of electronic components or optical components such as liquid crystal displays (LCDs), organic EL displays, touch panels using them, camera lens units, electronic devices, etc., to prevent defects from being generated during processing, assembly, inspection, transportation, etc. When surface protection is no longer needed, the surface protection film is removed from the optical component or electronic component. From the process of manufacturing the optical component or electronic component to the final shipment through the assembly process, inspection process, transportation process, etc., the same surface protection film is continuously used.
[0005] As a surface protection film, an acryl-based surface protection film using an acrylic resin in an adhesive layer is known in the art. However, since the acryl-based surface protection film has low wettability, bubbles can be trapped between the adherend and the surface protection film. In addition, since the acryl-based surface protection film may produce adhesive residues when peeled off, the acryl-based surface protection film is not suitable for protecting the surface of components such as optical components or electronic components that may be easily affected by foreign matter.
[0006] In recent years, surface protection films using a urethane binder resin in an adhesive layer have been reported in the art.
[0007] The background art of the present invention is disclosed in Korean Patent Publication No. 10-2012-0050136 and the like. Summary of the invention
[0008] An object of the present invention is to provide an adhesive film for surface protection which protects an adherend when the adhesive film is attached to the adherend and can be removed from the adherend without deforming and / or damaging the adherend.
[0009] Another object of the present invention is to provide an adhesive film for surface protection having good dent resistance.
[0010] A further object of the present invention is to provide an adhesive film for surface protection which has good dent resistance and can quickly recover to a non-dent state even when depressed.
[0011] Still another object of the present invention is to provide an adhesive film for surface protection which has a good appearance even after the adhesive film is left under high temperature / humidity conditions for a long time.
[0012] Still another object of the present invention is to provide an adhesive film for surface protection which allows less variation in peel strength even after the adhesive film is attached to an adherend and left at high temperature for a long time.
[0013] Still another object of the present invention is to provide an adhesive film for surface protection having low haze to ensure good optical properties.
[0014] According to one aspect of the present invention, an adhesive film for surface protection is provided.
[0015] The adhesive film for surface protection comprises a cured product of a composition for an adhesive film, wherein the composition for an adhesive film comprises a curable component containing a urethane-based binder, the adhesive film having a creep indentation (CI) value of less than 5%, an elastic indentation (EI) value of 350 MPa or more, a peel strength of 2.5 gf / inch or less, and a haze of 5% or less.
[0016] According to another aspect of the present invention, there is provided an adhesive sheet including the adhesive film according to the present invention.
[0017] According to a further aspect of the present invention, there is provided an optical member including an optical film and an adhesive film for surface protection formed on at least one surface of the optical film.
[0018] The present invention provides an adhesive film for surface protection, which protects an adherend when the adhesive film is attached to the adherend and can be removed from the adherend without deforming and / or damaging the adherend.
[0019] The present invention provides an adhesive film for surface protection having good dent resistance.
[0020] The present invention provides an adhesive film for surface protection which has good dent resistance and can quickly recover to a dent-free state even when pressed down.
[0021] The present invention provides an adhesive film for surface protection having a good appearance even after the adhesive film is left under high temperature / humidity conditions for a long time.
[0022] The present invention provides an adhesive film for surface protection which allows less variation in peel strength even after the adhesive film is attached to an adherend and left at high temperature for a long time.
[0023] The present invention provides an adhesive film for surface protection having low haze to ensure good optical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a cross-sectional view of an adhesive sheet including an adhesive film for surface protection according to the present invention.
[0025] Figure 2 This is a cross-sectional view of a sample used to measure pitting resistance, CI value, and EI value.
[0026] Figure 3 are photographs showing samples having no pits or having pits that were difficult to observe in the evaluation of pit resistance.
[0027] Figure 4 is a picture showing a sample having strongly visible pits in the pitting resistance evaluation. DETAILED DESCRIPTION
[0028] Hereinafter, embodiments of the present invention will be described in detail. However, it should be understood that the present invention is not limited to the following embodiments and can be embodied in different ways. The following embodiments are provided to enable those skilled in the art to thoroughly understand the present invention.
[0029] The terms used herein are for the purpose of describing exemplary embodiments and are not intended to limit the scope of the present invention.Herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0030] Herein, 'adherend' may include a glass plate, a plastic film, or a panel for a display device, but is not limited thereto.
[0031] Herein, "peel strength" is a value measured when an adhesive film is separated from an alkali-free glass plate provided as an adherend under the conditions of 23°C and 50% RH (relative humidity), a peel rate of 2,400 mm / min and a peel angle of 180° according to JIS Z0237.
[0032] In this article, the “CI value” is obtained by Figure 2 The values measured by the method shown in . Figure 2, a sample was prepared by sequentially stacking a black acryl plate 1, an adhesive film 2 for surface protection, and a base film 3. Then, a spherical tip 4 of a nanoindenter was placed at the center of the base film 3 of the sample (wherein the portion of the spherical tip contacting the base film had a sphere with a diameter of 0.4 mm), the sample was gradually pressed by the spherical tip for 20 seconds until the pressing load of the spherical tip reached 600 mN, and maintained at the load for 5 seconds, and then the force was released to obtain a CI value by automatic calculation of the nanoindenter.
[0033] In this article, “EI value” is obtained by Figure 2 The values measured by the method shown. Figure 2 , a sample was prepared by sequentially stacking a black acrylic plate 1, an adhesive film 2 for surface protection, and a base film 3. Then, a spherical tip 4 of a nano indenter was placed at the center of the base film 3 of the sample (wherein the portion of the spherical tip contacting the base film had a sphere with a diameter of 0.4 mm), the sample was gradually pressed by the spherical tip for 20 seconds until the pressing load of the spherical tip reached 600 mN, and maintained at the load for 5 seconds, and then the force was released to obtain the EI value by automatic calculation of the nano indenter.
[0034] The nanoindenter may be a Fischerscope HM2000LT (HELMUT-FISCHER), but is not limited thereto. The base film may have a thickness of 38 μm to 100 μm and may be a polymer film, for example, a polyester film, preferably a polyethylene terephthalate film. The sample may be a rectangular sample having a size of 100 mm x 50 mm (length x width). The black acryl plate may be an acryl plate having a thickness of 1,000 μm to 2,000 μm, for example, CL-885 (NITTO JUSHI KOGY).
[0035] The CI value and the EI value can be measured at 23° C. and 50% RH (relative humidity).
[0036] As used herein, "OH (hydroxyl) value" can be measured according to ASTM E 1899-08 and can be determined by, for example, a method using an Omnis Automatic Potentiometric Titrator System (Metrohm).
[0037] As used herein, "weight average molecular weight" can be obtained using gel permeation chromatography as a polystyrene standard.
[0038] As used herein, "number average molecular weight" can be obtained using gel permeation chromatography as a polystyrene standard.
[0039] Herein, "(meth)acryloyl" refers to acryloyl and / or methacryloyl.
[0040] As used herein, to express a specific numerical range, “X to Y” refers to a value greater than or equal to X and less than or equal to Y (X≤ and ≤Y).
[0041] According to one embodiment, the adhesive film for surface protection has a peel strength of 2.5 gf / inch or less. Within this range, the adhesive film for surface protection can be used as a process film, which temporarily protects the adherend when attached to the adherend and can be removed from the adherend as needed. The adhesive film can protect the adherend when attached to the adherend and can be easily peeled off from the adherend without deforming and / or damaging the adherend.
[0042] For example, the adhesive film can have a peel strength of greater than 0 gf / inch to 2.5 gf / inch (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 gf / inch, specifically, 0.8 gf / inch to 2.5 gf / inch, more specifically, 1 gf / inch to 2.4 gf / inch). Within this range, the adhesive film can protect the adherend, can be removed from the adherend without deforming and / or damaging the adherend, and can exhibit good reliability by preventing bubbles from being generated due to delamination at its edge when laser cutting the laminate of the adherend and the adhesive film.
[0043] Herein, “peel strength” refers to the initial peel strength of the adhesive film for surface protection and means the peel strength before the adhesive film is placed under high temperature or high temperature / humidity conditions.
[0044] In one embodiment, the adhesive film for surface protection has an EI value of 350MPa or more and a CI value of less than 5%. When the adhesive film has an EI value of 350MPa or more, the adhesive film can reduce the generation of pits during storage, transportation and other processes after being bonded to the substrate. When the adhesive film has a CI value of less than 5%, the adhesive film can show good pit resistance after being bonded to the substrate, thereby promoting the adhesive film to quickly return to a pit-free state even when pits appear during storage, transportation and other processes. For example, the adhesive film for surface protection can have an EI value of 350, 400, 450, 500, 550, 600MPa, 350MPa to 600MPa (specifically, 350MPa to 500MPa). For example, the adhesive film for surface protection can have a CI value of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5%, 1% to less than 5% (specifically, 2% to 4.5%).
[0045] According to one embodiment, when placed for a long time under high temperature / humidity conditions, the adhesive film for surface protection does not allow the outflow of components such as plasticizers derived from the adhesive film, thereby preventing pollution or poor appearance caused by plasticizers. Plasticizers do not react with other components in the adhesive film. Therefore, when placed for a long time under high temperature / humidity conditions, due to the outflow of plasticizers, conventional adhesive films may be contaminated or show poor appearance. When the adhesive film is placed for a long time under high temperature / humidity conditions, the pollution and appearance defects on the surface of this adhesive film can cause the peel strength of the adhesive film to increase, thereby making it difficult for the adhesive film to protect the adherend. In addition, after being adhered to the adherend, the adhesive film is subjected to the assembly process, inspection process and transportation process of a typical optical display. In such a plurality of processes, the laminate of the adhesive film and the adherend can be cut into a predetermined size. At this time, pollution and appearance defects cause defects in the cutting process. The adhesive film for surface protection according to one embodiment does not suffer from the above problems. This effect can be achieved by further including the following polyols in the following urethane binder.
[0046] In one embodiment, the adhesive film for surface protection can have a haze of 5% or less. Within this range, the adhesive film can show good cuttability and processability when cutting after being adhered to the adherend. For example, the adhesive film for surface protection can have a haze of 3% or less (specifically, 0 to 3%). The haze can be measured in the visible spectrum, for example, at a wavelength of 550nm.
[0047] In one embodiment, the adhesive film for surface protection may have good peel strength over time. Herein, "good peel strength over time" means that after the adhesive film is stacked on an adherend, the change in peel strength over time is low.
[0048] In one embodiment, the adhesive film may have a peel strength variation rate of -50% to 20% calculated according to Equation 1. Within this range, the adhesive film can protect the adherend even after being adhered to the adherend and placed under high temperature / humidity conditions for a long time, and can be removed from the adherend without deforming and / or damaging the adherend. Specifically, the adhesive film may have a peel strength variation rate of -50, -45, -40, -35, -30, -25, -20, -15, -10, -5, 0, 5, 10, 15, 20%, -30% to 20% calculated according to Equation 1:
[0049] Peel strength change rate = [(P2 - P1) / P1] x 100, (1)
[0050] Wherein, P1 represents the initial peel strength of the adhesive film relative to the alkali-free glass plate (unit: gf / inch), and
[0051] P2 represents the peel strength (unit: gf / inch) of the adhesive film with respect to the non-alkali glass plate after the adhesive film adhered to the non-alkali glass plate was left to stand at 85° C. and 85% RH for 250 hours.
[0052] In one embodiment, in Equation 1, P1 of the adhesive film may be 2.5 gf / inch or less, specifically 0.8 gf / inch to 2 gf / inch, more specifically 1 gf / inch to 2.4 gf / inch.
[0053] In one embodiment, in Equation 1, P2 of the adhesive film may be 2.5 gf / inch or less, specifically 0.8 gf / inch to 2 gf / inch, more specifically 1 gf / inch to 1.8 gf / inch.
[0054] In another embodiment, the adhesive film may have a peel strength variation rate of 0 to 40% calculated according to Equation 2. Within this range, the adhesive film may protect the adherend even after being adhered to the adherend and left under high temperature / humidity conditions for a long time, and may be removed from the adherend without deforming and / or damaging the adherend. Specifically, the adhesive film may have a peel strength variation rate of 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%,
[0055] Peel strength change rate = [(P3 - P1) / P1] x 100, (2)
[0056] Wherein, P1 represents the initial peel strength of the adhesive film relative to the alkali-free glass plate (unit: gf / inch), and
[0057] P3 represents the peel strength (unit: gf / inch) of the adhesive film with respect to the non-alkali glass plate after the adhesive film adhered to the non-alkali glass plate was left to stand at 50° C. for 3 days.
[0058] In one embodiment, in Equation 2, P1 of the adhesive film may be 2.5 gf / inch or less, specifically 0.8 gf / inch to 2 gf / inch, more specifically 1 gf / inch to 2.4 gf / inch.
[0059] In one embodiment, in Equation 2, P3 of the adhesive film may be 4.5 gf / inch or less, specifically 0.8 gf / inch to 4.5 gf / inch, more specifically 2 gf / inch to 4.5 gf / inch.
[0060] The adhesive film may have a thickness of 100 μm or less (eg, greater than 0 μm to 75 μm). Within this range, when attached to an adherend, the adhesive film may protect the adherend and may be easily removed from the adherend.
[0061] The adhesive film may include a cured product of the composition for an adhesive film. In one embodiment, the adhesive film may include a thermally cured product of the composition. Next, a composition for an adhesive film according to one embodiment of the present invention will be described.
[0062] The composition for an adhesive film comprises: a curable component containing a urethane-based binder, a polyol, and a curing agent.
[0063] Curable components
[0064] The curable component is cured by the curing agent to form a matrix of the adhesive film.
[0065] The curable component includes a urethane binder.
[0066] The urethane adhesive may include at least one urethane bond and at least one hydroxyl group (-OH). Since the urethane adhesive includes at least one hydroxyl group, the urethane adhesive may be cured by a curing agent to form a matrix of the adhesive film while providing peel strength.
[0067] In the curable component, the urethane adhesive can be present in an amount of 60wt% to 100wt%, 60, 65, 70, 75, 80, 85, 90, 95, 100wt% (specifically, 80wt% to 100wt%, more specifically, 95wt% to 100wt%). Within this range, the urethane adhesive can ensure the peel strength of the adhesive film while easily achieving the effects of the present invention.
[0068] The urethane adhesive can have a weight average molecular weight (Mw) of greater than 60,000 g / mol to less than 150,000 g / mol. Within this range, even after being placed for a long time under high temperature / humidity conditions, the adhesive film can also show good durability and good pit resistance. For example, the urethane adhesive has a weight average molecular weight of 65000, 70000, 75000, 80000, 85000, 90000, 95000, 100000, 105000, 110000, 115000, 120000, 125000, 130000, 135000, 140000, 145000 g / mol, 80,000 g / mol to 100,000 g / mol.
[0069] In one embodiment, the urethane-based adhesive may be a non-(meth)acrylic urethane-based adhesive containing no (meth)acryloyl group. With this component, the adhesive film can easily achieve the effects of the present invention.
[0070] The urethane-based adhesive may be prepared by reacting at least one type of polyol with at least one type of polyisocyanate compound. The urethane-based adhesive may be a random copolymer having units derived from the polyol.
[0071] The polyol may include at least one selected from polyether polyol, polyester polyol, polyacrylic polyol, polycaprolactone polyol and polycarbonate polyol. For example, the polyol may include at least one polyether polyol and may also include at least one polyester polyol.
[0072] The urethane adhesive may include units derived from polyether polyol. The urethane adhesive may also include units derived from polyester polyol. In this case, the urethane adhesive may easily achieve the effects of the present invention.
[0073] Polyether polyol can be the polyether polyol with alkylene oxide group and two or more hydroxyls, for example, difunctional polyether polyol (polyether diol) or trifunctional polyether polyol (polyether triol) such as polyethylene glycol, polypropylene glycol and polybutylene glycol (polytetramethylene glycol, polytetramethylene glycol), trifunctional polyether polyol (polyether triol) of glycerol alkylene oxide adduct (glycerin alkylene oxide adduct) etc.Therefore, urethane binder becomes hyperbranched binder, thus can have texturing structure rather than linear shape, thus more easily realize effect of the present invention.Hyperbranched binder refers to the polymer with multiple terminal functional groups and branched dendritic structure.
[0074] The polyether polyols can be used alone or in combination to prepare the urethane adhesive.
[0075] The polyether polyol may have a number average molecular weight of 400 to 10,000, 400, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000 (more particularly, 1,000 to 7,000). Within this range, the adhesive film may easily achieve the peel strength and modulus of the present invention while exhibiting good wettability.
[0076] The polyether polyol can be present in an amount of 50wt% to 100wt%, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100wt% (more particularly, 50wt% to 85wt%) of all polyols in the preparation of the urethane adhesive. Within this range, the polyether polyol can easily achieve the effects of the present invention.
[0077] Preferably, the polyether polyol includes a single polyether triol or a mixture of a polyether diol and a polyether triol, so that the effects of the present invention can be more easily achieved.
[0078] For example, in the preparation of urethane binder, polyether triol can be present in an amount of 50wt% to 95wt% (e.g., 50, 55, 60, 65, 70, 75, 80, 85, 90, 95wt%, 50wt% to 85wt%) of all polyols, and polyether diol can be present in an amount of 0wt% to 50wt% (e.g., 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50wt%, 0wt% to 40wt%, 0wt%) of all polyols. Within this range, the effect of the present invention can be easily achieved.
[0079] In one embodiment, the polyether diol may have a number average molecular weight of 400 to 10,000, 400, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000 (specifically, 1,000 to 6,000). Within this range, the adhesive film can easily achieve the peel strength of the present invention while showing good wettability.
[0080] In one embodiment, the polyether triol may have a number average molecular weight of 400 to 10,000, 400, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000 (specifically, 2,000 to 8,000). Within this range, the adhesive film can easily achieve the peel strength of the present invention while showing good wettability.
[0081] In one embodiment, the urethane-based adhesive may be prepared from a mixture of a polyol including 50 wt % to 95 wt % of a polyether triol and at least one polyisocyanate compound. Within this range, the urethane-based adhesive may easily achieve the effects of the present invention.
[0082] In one embodiment, the urethane-based binder may include a unit derived from a polyether polyol and a unit derived from a polyester polyol.
[0083] The polyester polyol may include a polyol obtained by esterification between at least one polyol and at least one acid component.
[0084] The polyol may include at least one selected from ethylene glycol, propylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 2-ethyl-1,3-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerol, trimethylolpropane, pentaerythritol and hexanetriol, but is not limited thereto. The acid component may include succinic acid, methylsuccinic acid, adipic acid, azelaic acid, sebacic acid, 1,12-dodecanoic acid, 1,14-tetradecanoic acid, dimer acid, 2-methyl-1,4-cyclohexanedicarboxylic acid (2-methyl-1,4-cyclohexanedicarboxylic acid), 2-ethyl-1,4-cyclohexanedicarboxylic acid (2-ethyl-1,4-cyclohexanedicarboxylic acid), terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid (1,4-naphthalenedicarboxylic acid), 4,4'-biphenyldicarboxylic acid (4,4'-biphenyldicarboxylic acid) and anhydrides thereof, but are not limited thereto.
[0085] The polyester polyols can be used alone or in combination to prepare the urethane adhesive.
[0086] The polyester polyol (eg, polyester diol or polyester triol) may have a number average molecular weight of about 1,000 to about 5,000 (specifically, about 2,000 to about 3,000). Within this range, the peel strength of the present invention may be advantageously achieved.
[0087] The polyester polyol may be present in an amount of 0 wt % to 50 wt % (specifically, 1 wt % to 50 wt %, more specifically, 5 wt % to 40 wt %) of all polyols in the preparation of the urethane-based binder. Within this range, the effects of the present invention may be easily achieved.
[0088] Polyester polyol can include polyester polyol with two or more hydroxyl groups, for example, difunctional polyester polyol (polyester diol) and / or trifunctional polyester polyol (polyester triol). Therefore, urethane binder becomes hyperbranched binder, thereby promoting the effect of the present invention. Preferably, polyester diol is used as polyester polyol.
[0089] In one embodiment, the urethane adhesive may be prepared from a mixture of a polyol including 50 wt % to 90 wt % of a polyether triol and 5 wt % to 40 wt % of a polyester triol and at least one polyisocyanate compound. Within this range, the effects of the present invention may be easily achieved.
[0090] The polyisocyanate compound may include a polyisocyanate compound with a plurality of isocyanate groups (-NCO). The polyisocyanate compound may be selected from any polyisocyanate compound known to those skilled in the art, and may include at least one selected from aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates and aromatic-aliphatic polyisocyanates. Preferably, the polyisocyanate compound is an aliphatic polyisocyanate.
[0091] The aliphatic polyisocyanate may include at least one selected from the following: hexamethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, propylene diisocyanate (including 1,2-propylene diisocyanate, etc.), butylene diisocyanate (including 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, etc.), dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate (including 2,4,4-trimethylhexamethylene diisocyanate, etc.), but is not limited thereto.
[0092] The polyisocyanate compound may be present in an amount of 1 to 10 parts by weight (specifically, 1 to 6 parts by weight, more specifically, 1 to 5.5 parts by weight) relative to 100 parts by weight of all polyols. Within this range, the urethane adhesive according to the present invention can be easily prepared.
[0093] The reaction may be performed by adding a catalyst to a mixture of at least one polyol and at least one polyisocyanate compound, and then reacting the mixture at a predetermined temperature.
[0094] The catalyst may be a tin compound and may include dibutyltin dilaurate (DBTDL), tin 2-ethylhexanoate, and the like, but is not limited thereto.
[0095] The urethane-based binder may be prepared by placing a polyol mixture in a reactor and heating the mixture at 80° C. to 100° C. for 10 to 30 minutes under nitrogen purge conditions to completely remove residual moisture, lowering the internal temperature of the reactor to 65° C. to 70° C., adding a polyisocyanate compound and a catalyst to the resulting product, and subjecting the resulting product to primary polymerization at 65° C. to 75° C. for 3 to 4 hours, and then subjecting the resulting product to secondary polymerization at 75° C. to 85° C. for 60 to 120 minutes.
[0096] In the curable component, the urethane-based binder may be present in an amount of 95 wt % or more (eg, 95 wt % to 100 wt %, specifically, 100 wt %). Within this range, the effects of the present invention may be easily achieved.
[0097] Polyols
[0098] In the adhesive film for surface protection, polyols are used to improve the pit resistance and prevent the plasticizer from flowing out after the adhesive film is placed under high temperature / humidity conditions for a long time. In addition, the urethane adhesive has a hydroxyl group and an isocyanate group at its end. By reacting with the remaining isocyanate group, the polyol makes it easy for the adhesive film to reach the EI and CI values according to the present invention.
[0099] Preferably, the polyol is a polyether polyol, more preferably a trifunctional polyether polyol. In this context, a trifunctional polyether polyol is a polyether polyol containing three hydroxyl groups. When combined with a urethane binder, the trifunctional polyether polyol can easily achieve the effects of the present invention.
[0100] The polyol may have a number average molecular weight (Mn) of 3,000 g / mol or more (preferably 6,000 g / mol or more, such as 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000 g / mol, 6,000 g / mol to 10,000 g / mol). When combined with a urethane binder, a polyol having a number average molecular weight (Mn) of 6000 g / mol or more can easily achieve the effects of the present invention.
[0101] Preferably, the polyol has an OH value of 10 mgKOH / g to 60 mgKOH / g (e.g., 20 mgKOH / g to 60 mgKOH / g, e.g., 20 mgKOH / g to 50 mgKOH / g). Within this range, the polyol can easily achieve the effects of the present invention when combined with a urethane binder.
[0102] In one embodiment, the polyether polyol can be a polyether polyol (polyether triol) having an alkylene oxide group and three hydroxyl groups, for example, a trifunctional polyether polyol (polyether triol) such as polyethylene glycol, polypropylene glycol, polybutylene glycol, a trifunctional polyether polyol (polyether triol) of a glycerol alkylene oxide adduct, and the like.
[0103] Preferably, the polyol may be a polyether triol. When combined with the above-mentioned binder, the polyether triol can easily achieve the effect of the present invention.
[0104] Preferably, the polyether polyol is polypropylene glycol. Polypropylene glycol has good flexibility and is inexpensive, thereby ensuring good economic feasibility.
[0105] Preferably, the polyol is a trifunctional triol having a weight average molecular weight of 6,000 g / mol or more and an OH value of 10 to 60 mgKOH / g. Within this range, the polyol can easily achieve the effects of the present invention when combined with the above binder.
[0106] Relative to 100 parts by weight of urethane adhesive, polyol can be present in an amount of 0.1 to 15 parts by weight (e.g., 0.1, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts by weight, specifically, 1 to 15 parts by weight, more specifically, 5 to 10 parts by weight). Within this range, by adding polyol, the effect can be achieved.
[0107] Curing agent
[0108] The curing agent can provide peel strength by curing the curable component.
[0109] The curing agent may have at least one isocyanate group (—NCO) that reacts with a hydroxyl group of a urethane-based binder and / or a polyol to form a matrix of the adhesive film and ensure peel strength of the adhesive film.
[0110] The isocyanate-based curing agent may be a multifunctional isocyanate-based curing agent having a plurality of isocyanate groups, and may include any typical isocyanate-based curing agent known to those skilled in the art.
[0111] In one embodiment, the isocyanate curing agent may include at least one selected from aliphatic isocyanates, alicyclic isocyanates, aromatic isocyanates and aromatic-aliphatic isocyanates, polyol adducts thereof, biuret thereof or isocyanurates thereof. For example, aliphatic isocyanates may include at least one selected from the following: hexamethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, propylene diisocyanate (including 1,2-propylene diisocyanate, etc.), butylene diisocyanate (including 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, etc.), dodecamethylene diisocyanate, trimethyl hexamethylene diisocyanate (including 2,4,4-trimethyl hexamethylene diisocyanate, etc.), but not limited thereto. For example, aromatic isocyanates may include at least one selected from toluene diisocyanate, xylene diisocyanate and phenylene diisocyanate, but not limited thereto.
[0112] Preferably, the isocyanate curing agent comprises isocyanurate of the above-mentioned isocyanate curing agent. When combined with the composition comprising the urethane binder and the plasticizer of the present invention, the isocyanurate curing agent can easily achieve the effect of the present invention.
[0113] Relative to 100 parts by weight of the curable component (specifically, urethane adhesive), for example, 100 parts by weight of urethane adhesive, the curing agent may be present in an amount of 6 to 20 parts by weight (e.g., 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts by weight, specifically, 6 to 15 parts by weight). Within this range, the curing agent may help form the adhesive film according to the present invention.
[0114] Plasticizers
[0115] In adhesive films for surface protection, plasticizers are used to improve anti-scattering properties. In this context, high anti-scattering properties mean that there is no particle or dust scattering when cutting the adhesive film, the adhesive film and the adherend.
[0116] The plasticizer may be selected from any ester plasticizer.
[0117] In one embodiment, the plasticizer may include C6 to C 18 Esters of monobasic or polybasic acids and branched alcohols having 18 or less carbon atoms, C 14 To C 18 Esters of unsaturated fatty acids or branched-chain acids and tetravalent or higher-valent alcohols, and C6 to C 10Esters of monoacids or polyacids and polyalkylene glycols. For example, the plasticizer may include isopropyl myristate, isopropyl palmitate, isostearyl palmitate, isostearyl laurate, diisostearyl adipate, diisohexadecyl sebacate, etc., but is not limited thereto.
[0118] The adhesive film may include at least one type of plasticizer, for example, two or more types of plasticizers.
[0119] Relative to 100 parts by weight of curable components (for example, urethane adhesive), plasticizer can be present in an amount of 10 to 30 parts by weight. Within this range, adhesive film can easily achieve CI value of the present invention. Preferably, relative to 100 parts by weight of curable components (for example, urethane adhesive), plasticizer is present in an amount of 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 parts by weight, 10 to 25 parts by weight, more preferably 15 to 25 parts by weight, and even more preferably 20 to 25 parts by weight.
[0120] The composition for an adhesive film may further include at least one selected from the group consisting of a cross-linking catalyst, a leveling agent, an antistatic agent, an antioxidant, and a retarder.
[0121] The cross-linking catalyst may catalyze the reaction between the curable component and the curing agent.
[0122] The cross-linking catalyst may include at least one metal catalyst. The metal catalyst may include a tin-based catalyst and / or a non-tin-based catalyst. Each of the tin-based catalyst and the non-tin-based catalyst may be selected from typical types known to those skilled in the art. For example, the tin-based catalyst may include dibutyltin dichloride, dibutyltin oxide, dibutyltin dilaurate, dibutyltin sulfide, dibutyltin diacetate, dibutyltin maleate, etc., but is not limited thereto.
[0123] The crosslinking catalyst may be present in an amount of 0.005 to 0.5 parts by weight (specifically, 0.005 to 0.1 parts by weight) relative to 100 parts by weight of the curable component (e.g., urethane-based adhesive). Within this range, the crosslinking catalyst may ensure a satisfactory pot life and rapid curing of the adhesive film.
[0124] The leveling agent can improve the leveling performance of the adhesive film, and can include acrylic leveling agents, fluorinated leveling agents, silicone leveling agents, silicone-acrylate leveling agents, and the like.
[0125] The leveling agent may be present in an amount of 0.1 to 5 parts by weight (specifically, 0.1 to 1 part by weight) relative to 100 parts by weight of the curable component (eg, urethane adhesive). Within this range, the leveling agent may ensure a low initial peel strength of the adhesive film.
[0126] The antistatic agent can prevent damage to the adherend by inhibiting the generation of static electricity in the process of peeling the adhesive film from the adherend after the adhesive film is adhered to the adherend. The antistatic agent can include typical antistatic agents known to those skilled in the art. For example, the antistatic agent can include an ionic liquid.
[0127] The antistatic agent may be present in an amount of 0.01 to 5 parts by weight (specifically, 0.01 to 1 part by weight) relative to 100 parts by weight of the curable component (e.g., urethane adhesive). Within this range, the antistatic agent may provide antistatic properties without affecting the properties of the adhesive film.
[0128] The antioxidant can prevent the influence of the external environment on the adhesive film, thereby ensuring its peel strength to inhibit the detachment of the adhesive film. The antioxidant can include typical antioxidants known to those skilled in the art. For example, the antioxidant can include cinnamate antioxidants, phenolic antioxidants, sulfur-based antioxidants, phosphorus-based antioxidants, HALS antioxidants, etc.
[0129] The antioxidant may be present in an amount of 0.01 to 5 parts by weight (specifically, 0.01 to 1 part by weight) relative to 100 parts by weight of the curable component (e.g., urethane adhesive). Within this range, the antioxidant may provide antioxidant properties without affecting the properties of the adhesive film.
[0130] The delay agent may include any typical delay agent known to those skilled in the art. For example, the delay agent may include acetylacetone or a complex thereof.
[0131] The retarder may be present in an amount of 0.01 to 5 parts by weight (specifically, 0.01 to 3 parts by weight) relative to 100 parts by weight of the curable component (e.g., urethane adhesive). Within this range, the retarder may provide delay performance without affecting the performance of the adhesive film.
[0132] The composition for the adhesive film may further include additives, such as UV absorbers, UV stabilizers, heat stabilizers, surfactants, fillers, pigments, etc., but are not limited thereto.
[0133] The adhesive film may be prepared by depositing the composition to a predetermined thickness on a base film to form a coating, and drying the coating at 110 to 140° C., followed by aging at 30 to 70° C. for 1 to 3 days, but is not limited thereto. After drying the coating, a release film may be stacked on the coating, followed by aging.
[0134] An adhesive sheet according to an embodiment includes an adhesive film for surface protection according to an embodiment. In one embodiment, the adhesive sheet may include an adhesive film for surface protection, a base film stacked on one surface of the adhesive film for surface protection, and a release film stacked on the other surface of the adhesive film for surface protection.
[0135] refer to Figure 1 The adhesive sheet includes an adhesive film 10 for surface protection, a base film 20 stacked on one surface of the adhesive film 10 , and a release film 30 stacked on the other surface of the adhesive film 10 .
[0136] The base film 20 can be used as a substrate to which the composition is applied when the adhesive film is formed by the composition for the adhesive film. The base film can be any typical polymer film known to those skilled in the art. For example, the base film can include at least one selected from the following: polyester resin, including polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, etc.; acryl resin (acryl resin, acrylic resin); cycloolefin polymer (COP) resin; cellulose ester resin, including triacetyl cellulose (TAC) and the like; polyvinyl acetate resin; polyvinyl chloride (PVC) resin; polynorbornene resin; polycarbonate (PC) resin; polyamide resin; polyacetal resin; polyphenylene ether resin; polyphenylene sulfide resin; polysulfone resin; polyether sulfone resin; polyarylate resin and polyimide resin. The base film can have a thickness of 10 μm to 200 μm (e.g., 50 μm to 100 μm).
[0137] When the adhesive film is formed using the composition for the adhesive film, the release film 30 is used to prevent the coating formed by the composition for the adhesive film from being contaminated by foreign matter, etc. The release film can be a typical polymer film known to those skilled in the art. For example, the release film can include at least one selected from the following: polyester resin, including polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, etc.; acryl resin; cycloolefin polymer (COP) resin; cellulose ester resin, including triacetyl cellulose (TAC), etc.; polyvinyl acetate resin; polyvinyl chloride (PVC) resin; polynorbornene resin; polycarbonate (PC) resin; polyamide resin; polyacetal resin; polyphenylene ether resin; polyphenylene sulfide resin; polysulfone resin; polyether sulfone resin; polyarylate resin and polyimide resin. The release film can have a thickness of 10 μm to 200 μm (e.g., 50 μm to 100 μm). The release film 30 may have at least one surface subjected to a release treatment with silicone or fluorine to facilitate peeling from the adhesive film.
[0138] Next, a method of using the adhesive sheet will be described.
[0139] When the release film is removed from the adhesive sheet, the adhesive film of the adhesive sheet is attached to an adherend. Then, when the adherend is no longer required to be protected, the entirety of the adhesive film and the base film for surface protection is removed from the adherend.
[0140] An optical member according to an embodiment of the present invention includes an optical film and an adhesive film for surface protection formed on at least one side of the optical film, wherein the adhesive film for surface protection includes the adhesive film for surface protection according to an embodiment of the present invention.
[0141] The optical film may include a polyimide film as a display panel. In one embodiment, the optical film may include a light emitting element layer and a polyimide film formed on at least one surface of the light emitting element layer. An organic insulating film or an inorganic insulating film may be further interposed between the optical film and the silicone adhesive protective film.
[0142] The optical component may also include a base film on the other surface of the adhesive film for surface protection. The base film can prevent the adhesive protective film from being contaminated by external foreign matter, etc. The base film may be an optical film formed of the same type of material as the above-mentioned optical film or a different type of material. For example, the base film may be a film formed of at least one selected from polyethylene terephthalate resin, polycarbonate resin, polyimide resin, poly (meth) acrylate resin, cycloolefin polymer resin and acrylic resin. The base film may have a thickness of 10 μm to 200 μm (e.g., 50 μm to 100 μm). Within this range, the base film may support the adhesive protective film.
[0143] Next, the present invention will be described in more detail with reference to examples. However, it should be understood that these examples are provided for illustration only and should not be construed in any way as limiting the present invention.
[0144] Preparation Example 1
[0145] In a 1,000 mL jacket reactor, 70 parts by weight of polyether polyol (PPG-3020), 15 parts by weight of polyether polyol (PPG-6000) and 15 parts by weight of polyester polyol (P-2010) were mixed under nitrogen purge conditions. Then, toluene was added to the mixture, stirred for 10 minutes, and then the mixture was heated to 85°C for 30 minutes under nitrogen purge conditions to remove residual moisture. The internal temperature of the reactor was reduced to 60°C and 4.5 parts by weight of hexamethylene diisocyanate (HDI) were added thereto. After the reactor was further stirred at 60°C for 10 minutes, 0.3 parts by weight of a polymerization catalyst (dibutyltin dilaurate (DBTDL)) was added to the resulting mixture. After 1 hour, the internal temperature of the reactor was raised to 70°C, and then raised to 80°C again after another hour, followed by polymerization at 80°C for 2 hours. Finally, a solution containing 65 wt % of a urethane-based binder (weight average molecular weight: 100,000 g / mol) in terms of solid content was obtained by diluting the resulting binder solution with toluene.
[0146] Example 1
[0147] A composition for an adhesive film comprising the components of Table 2 in terms of solid content was prepared by mixing 100 parts by weight of a urethane-based binder (Preparation Example 1), 10 parts by weight of polypropylene glycol (PPG-6000), 9.4 parts by weight of an isocyanate-based curing agent (Coronate HX), 0.24 parts by weight of a leveling agent (BYK-3700), 22.6 parts by weight of a plasticizer (isopropyl myristate (IPM)), 0.3 parts by weight of an antioxidant (Irganox 1010), 0.01 parts by weight of a cross-linking catalyst (Catalyst S, dibutyltin dilaurate (DBTDL)), and 9.4 parts by weight of a retarder (acetylacetone), and then adding toluene as a solvent to the mixture.
[0148] The prepared composition was deposited on the upper surface of a base film (PET film, thickness: 75 μm, TU67A, SKC) at a thickness of 75 μm using an applicator and dried at 130° C. for 4 min. Thereafter, a release film (PET film, thickness: 50 μm, product name: L3T, Youlchon Co., Ltd.) was attached to the coating and left at 50° C. for 2 days, thereby preparing an adhesive sheet in which a base film, an adhesive film for surface protection (thickness: 75 μm), and a release film were stacked in the stated order.
[0149] Examples 2 to 4
[0150] An adhesive sheet was prepared in the same manner as in Example 1, except that the type and / or content of each component in Example 1 was changed as listed in Table 2. In Table 2, "-" means that the corresponding component is absent and each component is expressed in parts by weight.
[0151] Comparative Examples 1 to 10
[0152] An adhesive sheet was prepared in the same manner as in Example 1, except that the type and / or content of each component in Example 1 was changed as listed in Table 3. In Table 3, "-" means that the corresponding component is absent and each component is expressed in parts by weight.
[0153] The components used in Examples and Comparative Examples are shown in Table 1.
[0154] The hydroxyl number, number average molecular weight and OH value listed in Table 1 can be obtained by referring to the product catalog.
[0155] [Table 1]
[0156]
[0157]
[0158] The compositions of the adhesive films for surface protection and / or the properties of the adhesive films for surface protection prepared in Examples and Comparative Examples were evaluated by the following methods.
[0159] (1) Indentation resistance (unitless): The adhesive sheet of base film / adhesive film for surface protection (thickness: 75 μm) / release film prepared in each of the examples and comparative examples was cut into a rectangular sample having a size of 100 mm×50 mm (length×width), and the release film was peeled off from the adhesive sheet. Then, the adhesive film of the adhesive sheet was adhered to a black acrylic plate (CL-885, thickness: 1,000 μm to 2,000 μm, Nitto Jushi Kogyo), thereby preparing a substrate having the following characteristics: Figure 2 Sample of the cross section shown. Figure 2, the pit resistance was evaluated on a sample including a black acrylic plate 1, an adhesive film 2 for surface protection, and a base film 3 stacked sequentially therein. Under the conditions of 23°C and 50% RH, the spherical tip 4 of the nanoindenter (FISCHERSCOPEHM2000LT, HELMUT-FISCHER) was placed at the center of the base film 3 of the sample (wherein the spherical tip portion contacting the base film had a sphere with a diameter of 0.4 mm), and the sample was gradually pressed by the spherical tip for 20 seconds until the pressing load of the spherical tip reached 600 mN, and maintained at the load for 5 seconds, and then the force was released. Then, the presence of pits was evaluated by visually observing the pressed shape on the surface of the black acrylic plate adjacent to the adhesive film. Figure 3 Samples with no pits or pits that are difficult to observe are shown, and Figure 4 A sample with strongly visible pits is shown. Figure 3 , there is no pit at the center of the sample, while the reference Figure 4 , there are wavy pits at the center of the sample.
[0160] ◎: No pits
[0161] ○: Usable because, although there are minute pit shapes, the pits are not easily visible.
[0162] Δ: Unusable due to the presence of multiple pits.
[0163] X: Unusable due to the presence of strongly visible pits.
[0164] (2) CI value (unit: %): The sample was prepared in the same manner as (1). The spherical tip 4 of the nanoindenter (FISCHERSCOPE HM2000LT, HELMUT-FISCHER) was placed at the center of the base film 3 of the sample (wherein the spherical tip portion in contact with the base film had a sphere with a diameter of 0.4 mm), and the sample was gradually pressed by the spherical tip for 20 seconds until the pressing load of the spherical tip reached 600 mN, and maintained at this load for 5 seconds, and then the force was released to obtain the CI value by automatic calculation of the nanoindenter.
[0165] (3) EI value (unit: %): The sample was prepared in the same manner as in (1). The spherical tip 4 of the nanoindenter (FISCHERSCOPE HM2000LT, HELMUT-FISCHER) was placed at the center of the base film 3 of the sample (wherein the spherical tip portion in contact with the base film had a sphere with a diameter of 0.4 mm), and the sample was gradually pressed by the spherical tip for 20 seconds until the pressing load of the spherical tip reached 600 mN, and maintained at this load for 5 seconds, and then the force was released to obtain the EI value by automatic calculation of the nanoindenter.
[0166] (4) Initial peel strength (unit: gf / inch): The adhesive sheet of release film / adhesive film for surface protection / base film prepared in each of the Examples and Comparative Examples was cut into a size of 200 mm x 25 mm (length x width), and the release film was removed from the adhesive sheet to expose the adhesive film. An alkali-free glass plate was stacked on the exposed surface of the adhesive film, and then a 2 kg roller was reciprocated on the glass plate 3 times to prepare a sample of a laminate having an alkali-free glass plate / adhesive film / base film.
[0167] The peel strength was measured according to JIS Z0237. The peel strength of the sample was measured using a tensile tester (Textureanalyzer, TA Industry) as a peel strength tester when the adhesive film was peeled off from an alkali-free glass plate at a peeling speed of 2,400 mm / min and a peeling angle of 180° under peeling conditions of 23°C and 50% RH. The peel strength was measured three times and then averaged.
[0168] (5) Peel strength after 3 days at 50°C (unit: gf / inch): A sample of a laminate having an alkali-free glass plate / adhesive film / base film was prepared in the same manner as in (4). The prepared sample was left at 50°C for 3 days. Then, the peel strength was measured in the same manner as in (4).
[0169] (6) Appearance after testing under high temperature / humidity conditions (elution of plasticizer) (unitless): The laminate of the release film / adhesive film for surface protection / base film prepared in each of the examples and comparative examples was left at 85° C. and 85% RH for 250 hours. The elution of the plasticizer was checked on the adhesive film surface. The elution of the plasticizer was checked with the naked eye. The sample with a clean surface of the adhesive film was rated as "good" due to the absence of elution of the plasticizer, while the sample with an unclean surface of the adhesive film was rated as "poor" due to the elution of the plasticizer.
[0170] (7) Optical properties (unit: %): After removing the base film and the release film from the adhesive sheet of each embodiment and comparative example in which the base film, the adhesive film for surface protection (thickness: 75 μm) and the release film were stacked in the stated order, the optical properties of the adhesive film for surface protection were measured using a haze meter (NDH-2000, Nippon-Denshoku) under the conditions of 23° C. and 50% RH.
[0171] [Table 2]
[0172]
[0173]
[0174] [Table 3]
[0175]
[0176] As shown in Table 2, the adhesive film for surface protection according to the present invention exhibits good dent resistance, has a peel strength that protects an adherend, can be removed from an adherend without deforming and / or damaging the adherend when removed from the adherend after being adhered to the adherend, does not generate bubbles due to edge delamination when a laminate of the adhesive film and the adherend is cut, and exhibits a good appearance even after being left for a long time under high temperature / humidity conditions.
[0177] On the other hand, as shown in Table 3, the adhesive films prepared in the comparative examples failed to provide all the effects of the present invention.
[0178] It should be understood that various modifications, changes, variations and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.
Claims
1. An adhesive film for surface protection, comprising a cured product of a composition for the adhesive film, the composition comprising: a curable component containing a urethane binder, in, The adhesive film for surface protection has a creep indentation value of less than 5%, an elastic indentation value of 350 MPa or more, a peel strength of 2.5 gf / inch or less, and a haze of 5% or less.
2. The adhesive film for surface protection according to claim 1, wherein The composition also comprises a polyol.
3. The adhesive film for surface protection according to claim 2, wherein The polyol is a trifunctional polyether polyol.
4. The adhesive film for surface protection according to claim 2, wherein The polyol has a number average molecular weight of 3,000 g / mol or more.
5. The adhesive film for surface protection according to claim 2, wherein The polyol has a hydroxyl value of 10 to 60 mgKOH / g.
6. The adhesive film for surface protection according to claim 2, wherein The polyol is present in an amount of 0.1 parts by weight to 15 parts by weight relative to 100 parts by weight of the curable component.
7. The adhesive film for surface protection according to claim 1, wherein The urethane-based binder includes a unit derived from a polyether polyol and a unit derived from a polyester polyol.
8. The adhesive film for surface protection according to claim 7, wherein The polyether polyol is a polyether triol.
9. The adhesive film for surface protection according to claim 7, wherein The polyester polyol is a polyester triol.
10. The adhesive film for surface protection according to claim 7, wherein The urethane-based binder is derived from a polyol comprising 50 wt % to 90 wt % of a polyether triol and 5 wt % to 40 wt % of a polyester triol, based on the total weight of all polyols in the preparation of the urethane-based binder.
11. The adhesive film for surface protection according to claim 1, wherein The urethane-based binder is present in the curable component in an amount of 95 wt % or more.
12. The adhesive film for surface protection according to claim 1, wherein The composition also includes a curing agent.
13. The adhesive film for surface protection according to claim 12, wherein The curing agent is present in an amount of 6 to 20 parts by weight relative to 100 parts by weight of the curable component.
14. The adhesive film for surface protection according to claim 1, wherein The composition also includes a plasticizer.
15. The adhesive film for surface protection according to claim 14, wherein The plasticizer is present in an amount of 10 to 30 parts by weight relative to 100 parts by weight of the curable component.
16. The adhesive film for surface protection according to claim 14, wherein The plasticizer comprises at least one of the following: C6 to C 18 Esters of monobasic or polybasic acids and branched alcohols having 18 or fewer carbon atoms, C 14 To C 18 Esters of unsaturated fatty acids or branched-chain acids and tetravalent or higher-valent alcohols, and C6 to C 10 Esters of monobasic or polybasic acids and polyalkylene glycols.
17. The adhesive film for surface protection according to claim 1, wherein The adhesive film has a peel strength variation rate of 0 to 40% according to Equation 2: Peel strength change rate = [(P3 – P1) / P1] x 100, (2) Wherein, P1 represents the initial peel strength of the adhesive film relative to the alkali-free glass plate, unit: gf / inch, and P3 represents the peel strength of the adhesive film with respect to the non-alkali glass plate after the adhesive film adhered to the non-alkali glass plate is left at 50° C. for 3 days, and the unit is gf / inch. 18 . The adhesive film for surface protection according to claim 1 , further comprising: at least one of a cross-linking catalyst, a leveling agent, an antistatic agent, an antioxidant, and a retarder. 19 . An adhesive sheet comprising the adhesive film for surface protection according to claim 1 .
20. An optical component, comprising: Optical films; as well as The adhesive film for surface protection according to any one of claims 1 to 18, wherein the adhesive film is formed on at least one surface of the optical film.
Citation Information
Patent Citations
Silicon pressure-sensitive adhesive composition for window film with excellent rework porperties and compatibility and window film using the silicon pressure-sensitive adhesive
KR1020120050136A
Light emitting device and electronic apparatus including the same
KR1020230095134A